Drosophila melanogaster as a model for human intestinal infection and pathology - Yiorgos Apidianakis; Laurence G. Rahme (The Company of Biologists, 2011)
Recent findings concerning Drosophila melanogaster intestinal pathology suggest that this model is well suited for the study of intestinal stem cell physiology during aging, stress and infection. Despite the physiological divergence between vertebrates and insects, the modeling of human intestinal diseases is possible in Drosophila because of the high degree of conservation between Drosophila and mammals with respect to the signaling pathways that control intestinal development, regeneration and disease. Furthermore, the genetic amenability of Drosophila makes it an advantageous model species. The well-studied intestinal stem cell lineage, as well as the tools available for its manipulation in vivo, provide a promising framework that can be used to elucidate many aspects of human intestinal pathology. In this Perspective, we discuss recent advances in the study of Drosophila intestinal infection and pathology, and briefly review the parallels and differences between human and Drosophila intestinal regeneration and disease.